FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU ETIS MAHASISWA AKUNTANSI UNIVERSITAS BAKRIE - Lucyanda, Jurica; Endro, Gunardi (Media Riset Akuntansi, 2012)
The  study  aims  to  examine  some  factors  that  may  influence  ethical  attitude  of  accounting students  of Bakrie University. The factors used  in this study  are factors  of individual, namely : intellectual  intelligence,  emotional  intelligence,  spiritual  intelligence,  gender,  locus  of  control and  equity  sensitivity.  The  respondents  are  the  accounting  students  of  Bakrie  University  who have  attended  courses  in  Auditing.  Data  were  collected  using  survey  with  personally administrative  questionnaire  technique.  Total  number  of  samples  was  110  respondents.  Data analysis  used  multiple  regression  analysis.  The  result  shows  that  emotional intelligence  is the only  factor  that  affects  ethical  attitude  of  the  accounting  students  of  Bakrie  University.  The result  supports the argument  of Aristotelian  ethics that  emphasizes  the effect of  character and practical  wisdom  (emotional  intelligence)  on  ethical  attitude  of  individuals.  Thus,  the  result underlines  the  importance  of  building  moral  character  in  accounting  education. Keywords:  ethical  attitude,  intellectual  intelligence,  emotional  intelligence,  spiritual  intelligence,  gender,  locus  of  control,  equity  sensitivity.